2022
DOI: 10.1182/bloodadvances.2020004136
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of DNMT3A mutation in acute myeloid leukemia with mutated NPM1

Abstract: The negative prognostic impact of FLT3-ITD in patients with acute myeloid leukemia with mutated NPM1 (AML-NPM1) is restricted to patients with a higher FLT3-ITD allelic ratio (≥0.5; FLT3high) and considered negligible in wild-type (FLT3wt)/low ITD ratio (FLT3low) patients. Since the co-mutation of DNMT3A (DNMT3Amut) has been suggested to negatively influence the prognosis of AML-NPM1, we analyzed DNMT3Amut impact in FLT3-ITD subsets (absent, low and high ratio). A total of 164 patients diagnosed with AML-NPM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Then further analysis revealed that there was no difference regarding EFS and OS between patients with first-class mutation and patients without first-class mutation. As known, the firstclass mutations included prognostic genes such as CEBPA, FLT3, DNMT3A, NPM1, and RNF213; they are previously observed to correlate with prognosis of AML [28][29][30]. However, our study indicated that the mutated genes might not be correlated with survival in patients with relapsed AML after allo-HSCT, which might result from the reduced small sample size in our study; this presumption needed more validation by future studies.…”
Section: Discussionmentioning
confidence: 60%
“…Then further analysis revealed that there was no difference regarding EFS and OS between patients with first-class mutation and patients without first-class mutation. As known, the firstclass mutations included prognostic genes such as CEBPA, FLT3, DNMT3A, NPM1, and RNF213; they are previously observed to correlate with prognosis of AML [28][29][30]. However, our study indicated that the mutated genes might not be correlated with survival in patients with relapsed AML after allo-HSCT, which might result from the reduced small sample size in our study; this presumption needed more validation by future studies.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, this category includes patients with cytogenetic abnormalities not classified as favorable or adverse, as well as patients without NPM1 mutation and adverse-risk genetic lesions, which are biologically heterogeneous 29,40 . In this context, further knowledge on the prognostic impact of additional markers and gene mutation interactions, such as the deleterious effect associated with BCOR, SETBP1, ZRSR2 or DNMT3A co-mutations might contribute to redefine the current classification in future updates, as suggested by Eisfeld et al from the CALGB network 20,41 .…”
Section: Discussionmentioning
confidence: 99%
“…29,40 In this context, further knowledge on the prognostic impact of additional markers and gene mutation interactions, such as the deleterious effect associated with BCOR , SETBP1, ZRSR2 , or DNMT3A comutations might contribute to redefine the current classification in future updates, as suggested by Eisfeld et al 20 from the CALGB network. 41 …”
Section: Discussionmentioning
confidence: 99%
“…In de novo adult AML, NPM1 is most frequently mutated with DNMT3A, 39 and the majority of DNMT3A mutations are found in R882, replicated by the murine R878 model used in our study. Recent analysis aimed to elucidate the prognostic impact of cooccurring DNMT3A and NPM1 mutations in AML has found that DNMT3A mutation status does not have an overall prognostic impact 40 ; however, DNMT3A mut was associated with significantly higher measurable residual disease (MRD) compared with DNMT3A wt , and DNMT3A mut patients exhibited a trend toward a greater risk of molecular relapse. Based on our results, we speculate that the cell of origin incurring and sustaining the NPM1 cooperating mutation will have an impact on disease prognosis and may be a relevant consideration when evaluating MRD.…”
Section: Discussionmentioning
confidence: 99%